The First Chalcone Derivatives of Valine-Based Spiro-Cyclotriphosphazenes: In Vitro Cytotoxic Properties, Molecular Docking and DNA Damage Mechanism Studies - Yucel, Yunus; Seker, Ferhan Sultan; Erden, Busra Aksoy; Ozdemir, Mucahit; Tekin, Cigdem; Caliskan, Eray; Biryan, Fatih (Wiley, 2025)
Cancer treatment requires novel compounds with potent cytotoxic and genotoxic properties to effectively target cancer cells. In this study, new hybrid cyclotriphosphazene compounds were synthesized, characterized, and evaluated for their biological activity. Cytotoxicity against A2780 and Caco-2 cancer cell lines was assessed via the MTT assay, while genotoxic effects at 60-70% cell viability were examined using the Comet assay. Apoptotic cells were identified through TUNEL analyses, and reactive oxygen species levels were measured. Results showed that these compounds significantly reduced cell viability through DNA damage mechanisms. At high doses (50-100 mu M), BV, BVK1, BVK2, and BVK4 decreased A2780 cell viability by 30-65%, whereas VPA had a milder effect (15-25%). In Caco-2 cells, viability was reduced by 10-35%. The compounds exhibited varying cytotoxicity across different cancer cell lines, reflecting cancer cell heterogeneity. Significant DNA damage, including changes in tail length, tail density, and tail moment, was observed in A2780 cells, confirming cell death via DNA damage. Molecular docking analyses further supported the potential of cyclotriphosphazene compounds (BV and BVK2) as targeted cancer inhibitors. Molecular docking revealed BVK2's high selectivity for Bcl-2, mutant p53, and VEGFR2. BVK2 and BV demonstrate strong binding affinities with key cancer-related targets, indicating their potential as multi-targeted inhibitors that regulate apoptosis, cell cycle control, and angiogenesis, making them promising candidates for targeted cancer therapy.
Keywords: cyclotriphosphazene; cytotoxicity; genotoxicity; molecular docking; TUNEL analysis